Potential applications of the CRISPR/Cas technology for genetic improvement of yam (Dioscorea spp.) - Syombua, E.D.; Tripathi, J.; Obiero, G.; Nguu, E.; Yang, B.; Wang, K.; Tripathi, L. (Wiley, 2022)
Yam (Dioscorea spp.) is an economically important crop grown in the tropical and subtropical regions, producing tuberous roots that serve as a staple food, an income source, and an excellent source of various pharmaceutical precursors. Yam production is constrained by disease and pest infestations and a range of abiotic stresses. Genetic improvement can significantly mitigate these challenges, improve productivity, expand the yam markets, and increase economic gains. However, several intrinsic attributes of the crop have curtailed progress in yam breeding. Advanced genetic engineering such as genome editing by sequence-specific nucleases has emerged as complementary approaches to conventional breeding techniques. Mainly, the clustered regularly interspaced short palindromic repeats/CRISPR-associated protein (CRISPR/Cas) system for genome editing has provided robust platforms for gene function analysis and crop improvement in the post-genomic era. Despite its significance, research towards improving the yam species remains under-represented compared to other staple tuber crops such as cassava and sweet potato. Thus, it is critical to explore avenues for increasing the genetic gains from this under-exploited crop. The present review focuses on the progress and prospects for applying the CRISPR/Cas technology for yam improvement. The study elaborates on the currently available CRISPR/Cas tool for yam genome engineering and explores the potential applications of this toolkit in mitigating the various challenges encountered in yam production and consumption. Furthermore, we have delved into the challenges associated with this technology and the improvements made to minimize these challenges. The insights presented herein provide a guide for yam improvement to increase genetic gains from this under-researched and under-utilized resource.